COVID-19 and Private Higher Education - Levy, Daniel (International Higher Education, 2021)
Significant and identifiable differences and similarities surface between private and public higher education regarding COVID-19 policies and impacts. The same holds for differences and similarities between different parts of the private sector. Whereas private institutions are on average at higher risk from COVID impacts, and demand-absorbing ones are predictably at the greatest risk, there are offsetting factors as well, including certain advantages regarding private policy making autonomy and flexibility.